Pengaruh Kualitas Produk, Pemasaran Media Sosial dan Persepsi Harga terhadap Keputusan Pembelian di Remaja Bakehouse - Putri Nur’Aini Zahrah; Darwin Raja Unggul Saragih (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study was conducted to analyze the partial and simultaneous influences of product quality variables, social media marketing, and price perception on purchasing decisions of Remaja Bakehouse consumers. This study used a survey method with quantitative approach was applied to collect primary data from 135 Bakehouse Adolescent consumers. Respondent were selected non-probabilistically via a questionnaire. Data analysis used multiple linear regression method with SPSS version 25, wich includedvalidity testing, reliability testing, classis assumption tesing in the form of linearity, as well as statistical testing. The hypothesis test indicates that product quality, social media marketing, and price perception have a simultaneous significant influence on purchase decisions. In part, only the variables of product quality and social media marketing were shown to have a positive and significant effect, while price perception did not show a significant influence. Based on the value of the coefficient of determination, the three independent variables explained 88.4% of the variation in purchasing decisions, with the remaining 11.6% attributable to external factors outside the model. The study recommends that Remaja Bakehouse maintain consistent product quality in taste, texture, and appearance to strengthen its competitive advantage. Optimizing interactive marketing strategies through social media is also needed to expand market reach. In addition, adjustments to pricing strategies that are competitive and aligned with consumer benefits need to be made so that brand preferences remain strong in the culinary industry's competitive landscape.